Valve Corporation’s Evolution from a Game Developer to the Gaming Titan - Zhao, Tinghui (Transactions on Social Science, Education and Humanities Research, 2024)
This research paper delves into Valve Corporation’s multifaceted competitive strategy within the digital gaming industry, exploring its evolution from a pioneering game developer to an influential entity in digital distribution, e-sports, and hardware innovation. This study starts from study the history of Valve and how it changes from video game developer to digital distributor. Central to the analysis of this paper is Steam, Valve’s digital distribution platform, which has redefined game sales and community engagement. Author further examines Valve’s strategic involvement in e-sports, through major tournament and in game activates to highlighting its impact on competitive gaming culture and industry standards. Additionally, author assess Valve’s ventures into hardware development, including the Steam Deck and Valve Index, as extensions of its ecosystem. Through qualitative analysis, this paper explores how these integrated strategies reinforce Valve’s market position, drive industry-wide innovation, and shape future gaming trends. These findings underscore Valve’s role as a dynamic force in the gaming industry, adept at navigating and influencing the digital age of gaming.